ChemInform Abstract: Organocatalytic Enantioselective Desymmetrisation. Issue 49 (17th November 2016) - Borissov, A.; Davies, T. Q.; Ellis, S. R.; Fleming, T. A.; Richardson, M. S. W.; Dixon, D. J.
Abstract: Review: 247 refs.